1971
DOI: 10.1071/ch9710243
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of transition metal fluorides. VIII. Reactions of rhenium heptafluoride and hexafluoride

Abstract: Oxidation-reduction and halogen-exchange reactions of the higher fluorides of rhenium with a series of selected reagents have been investigated. The results correlate with studies of reactivities of higher fluorides of other transition metals previously reported. The reactions reported provide markedly improved preparative routes to the hexachloride, pentabromide, and pentafluoride of rhenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

1975
1975
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…In a typical reaction, 30 mg of Si powder and 10 ml of anhydrous HF are combined in a Kel-F tube with a Teflon-coated stir bar. The slurry is stirred at room temperature for up to 12 hr and the pressure in the system monitored with a metal-diaphragm pressure transducer. The slurry is frozen periodically, e.g., every hour, and any noncondensable gas pumped off.…”
Section: Methodsmentioning
confidence: 99%
“…In a typical reaction, 30 mg of Si powder and 10 ml of anhydrous HF are combined in a Kel-F tube with a Teflon-coated stir bar. The slurry is stirred at room temperature for up to 12 hr and the pressure in the system monitored with a metal-diaphragm pressure transducer. The slurry is frozen periodically, e.g., every hour, and any noncondensable gas pumped off.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of a red-to-brown volatile intermediate has also been observed in the reactions of rhenium hexafluoride with titanium tetrachloride and carbon tetrachloride, although the ultimate product in each case was rhenium hexachloride. 44 It was suggested that this intermediate was a mixed chloride fluoride of rhenium(VI), perhaps ReF5Cl. This volatile red compound has actually been isolated from the reaction between rhenium pentachloride and elemental fluorine at 30 °C.45 It is thermally unstable above -30 °C, giving rhenium hexafluoride and rhenium chlorides.…”
Section: (E -A) + 2dmentioning
confidence: 99%
“…Genau das ist ja der Fall im ReF 6 . [13][14][15][16] In jüngerer Zeit wurde berichtet, dass ReCl 6 À elektrochemisch offensichtlich zu ReCl 6 oxidiert werden kann. Zunächst sollte es bei der Chlorierung von Rheniummetall bei 600 8C erhalten worden sein, [12] was von anderen Arbeitsgruppen bezweifelt wurde.…”
Section: Rheniumhexachloridunclassified
“…[18] Über die Herstellung von ReCl 6 gibt es widersprüchliche Angaben. [17] Die Fluor-Chlor-Austauschmethode, die wir zur Herstellung des MoCl 6 genutzt haben, wurde auch von anderen schon zur Herstellung von ReCl 6 versucht, [12,13,15] aber offensichtlich wurden nur verunreinigte Produkte erhalten. [13][14][15][16] In jüngerer Zeit wurde berichtet, dass ReCl 6 À elektrochemisch offensichtlich zu ReCl 6 oxidiert werden kann.…”
Section: Rheniumhexachloridunclassified
See 1 more Smart Citation